Impact of global cerebral ischemia on K+ channel expression and membrane properties of glial cells in the rat hippocampus - Pivonkova, Helena; Benesova, Jana; Butenko, Olena; Chvatal, Alexandr; Anderova, Miroslava (Neurochemistry international, 2010)
Astrocytes and NG2 glia respond to CNS injury by the formation of a glial scar. Since the changes in K(+) currents in astrocytes and NG2 glia that accompany glial scar formation might influence tissue outcome by altering K(+) ion homeostasis, we aimed to characterize the changes in K(+) currents in hippocampal astrocytes and NG2 glia during an extended time window of reperfusion after ischemic injury. Global cerebral ischemia was induced in adult rats by bilateral, 15-min common carotid artery occlusion combined with low-pressure oxygen ventilation. Using the patch-clamp technique, we investigated the membrane properties of hippocampal astrocytes and NG2 glia in situ 2 hours, 6 hours, 1 day, 3 days, 7 days or 5 weeks after ischemia. Astrocytes in the CA1 region of the hippocampus progressively depolarized starting 3 days after ischemia, which coincided with decreased Kir4.1 protein expression in the gliotic tissue. Other K(+) channels described previously in astrocytes, such as Kir2.1, Kir5.1 and TREK1, did not show any changes in their protein content in the hippocampus after ischemia; however, their expression switched from neurons to reactive astrocytes, as visualized by immunohistochemistry. NG2 glia displayed increased input resistance, decreased membrane capacitance, increased delayed outwardly rectifying and A-type K(+) currents and decreased inward K(+) currents 3 days after ischemia, accompanied by their proliferation. Our results show that the membrane properties of astrocytes after ischemia undergo complex alterations, which might profoundly influence the maintenance of K(+) homeostasis in the damaged tissue, while NG2 glia display membrane currents typical of proliferating cells.
Keywords: down regulace; Membrane Potentials; Male; draslíkové kanály dovnitř usměrňující; Rats, Wistar; kanál KCNJ10; polarita buněk; hipokampální oblast CA1; Gliosis; mužské pohlaví; potkani Wistar; ischemie mozku; membránové potenciály; krysa rodu Rattus; Cell Membrane; Animals; Down-Regulation; Cell Polarity; zvířata; buněčná membrána; CA1 Region, Hippocampal; Rats; neuroglie; Neuroglia; Kcnj10 Channel; glióza; Potassium Channels, Inwardly Rectifying; Brain Ischemia